2017
DOI: 10.1002/smll.201700796
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Blowing‐Induced Porous Cobalt Phosphide/Nitrogen‐Doped Carbon Nanostructures with Enhanced Electrochemical Oxidation Performance toward Water and Other Small Molecules

Abstract: Rational design of high active and robust nonprecious metal catalysts with excellent catalytic efficiency in oxygen evolution reaction (OER) is extremely vital for making the water splitting process more energy efficient and economical. Among these noble metal-free catalysts, transition-metal-based nanomaterials are considered as one of the most promising OER catalysts due to their relatively low-cost intrinsic activities, high abundance, and diversity in terms of structure and morphology. Herein, a facile sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 68 publications
(90 reference statements)
4
29
0
Order By: Relevance
“…If their [a] N-GNT:N-doped graphenen anotube. [89] The proposed mechanism is consistent with the recently reported excellent electrocatalytic performance of N-doped graphene decorated with Fe-modifiedC oOOH nanoparticles. [88] The higher the 2p band centero fl attice oxygen, the more oxygen molecules are generated.…”
Section: Heterojunction Strategies For the Oersupporting
confidence: 89%
See 2 more Smart Citations
“…If their [a] N-GNT:N-doped graphenen anotube. [89] The proposed mechanism is consistent with the recently reported excellent electrocatalytic performance of N-doped graphene decorated with Fe-modifiedC oOOH nanoparticles. [88] The higher the 2p band centero fl attice oxygen, the more oxygen molecules are generated.…”
Section: Heterojunction Strategies For the Oersupporting
confidence: 89%
“…[88] In detail, upon increasing the covalency of MÀOi nT Mo xides (e.g.,t he covalencyo fC o ÀOi ncreasesf rom LaCoO 3 to SrCoO 3 ), the 2p band centers of lattice oxygen becomeh igher. [89] The negatively shifted peak of Co in the 2p X-ray photoelectron( XPS) spectrum and the enhanced response of the hydroxy (ÀOH) groups in the 1s XPS spectrum jointly revealt hat an oxygen compound of Co with ah igher oxidation level is generated. Figure 10).…”
Section: Heterojunction Strategies For the Oermentioning
confidence: 99%
See 1 more Smart Citation
“…Further analysis indicated that the improved performance was attributed to the increased hydrogen absorption ability as well as the oxophilic nature of surface phosphorus atoms. In comparison, nonnoble metal TMPs are also promising but their performance for these reactions is usually poorer as compared with that of noble TMPs . Aside from these, the electrocatalytic behaviors of TMPs toward organic molecules also extend their application to biosensors .…”
Section: Applicationsmentioning
confidence: 99%
“…Successively, recent studies proved that TMPs can also serve as highly efficient catalysts or precatalysts in oxygen evolution/reduction, which extends their applications to water electrolyzer, metal–air batteries, and fuel cells . Besides, the burgeoning electrocatalytic applications of TMPs in CO 2 electrochemical reduction, and organic molecules electrocatalysis, along with regulation of the polysulfide redox conversion in lithium–sulfur (Li–S) batteries, raise TMPs again to be a research hotspot.…”
Section: Introductionmentioning
confidence: 99%